Aerodynamic Approach to Two-Passenger City Car Design: A Study of Square Back and Compact Shapes - Randi Purnama Putra; Dori Yuvenda; Remon Lapisa; Wanda Afnison; Milana Milana; M. Yasep Setiawan; Ahmad Arif; Dani Harmanto (Universitas Muhammadiyah Magelang, 2025)
The development of lightweight electric cars for urban mobility requires efficient aerodynamic design without sacrificing space efficiency. This study presents a novel method by investigating the combination of a two-seater city car's compact dimensions and square back shape, which has not been extensively researched for low- to medium-velocity vehicles. This study's objective is to assess the design's aerodynamic performance using numerical simulations using the Computational Fluid Dynamics (CFD) approach. The vehicle model is designed with a compact body and square back, which is commonly used in small vehicles with high maneuverability requirements. The simulations are conducted at three different air velocity levels: 10, 20, and 30 m/s. The results of the study showed an increase in the value of the drag coefficient (Cd) along with an increase in flow velocity. At a velocity of 10 m/s, the Cd value was recorded at 0.4536. When the velocity increased to 20 m/s, the drag coefficient increased slightly to 0.4563. Further increases in velocity to 30 m/s resulted in a Cd value of 0.4581. This Cd value shows the consistency of aerodynamic performance with increasing velocity, with fluctuations that remain within the efficiency limits of lightweight vehicles. The pressure distribution contour shows high-pressure accumulation at the front and low pressure at the rear of the vehicle, which generates large turbulent wakes in the rear area and contributes to increased drag. These findings indicate that the square rear body design faces significant aerodynamic challenges. Therefore, design strategies such as adding a rear spoiler, using a rear diffuser, and optimizing the rear body angle are suggested as potential solutions to improve flow efficiency.